Eventos adversos infecciosos relacionadosà gastroplastia: análise retrospectiva de 05 anos (2007 2011) - Felipe Haunk Mansur (2014)
The morbid obesity is a disease which affects increasing number individuals, and in its most severe ways it is related to catastrophic medical consequences. It is considered the second cause of preventable death. The gastroplasty (bariatric surgery) is the only viable therapeutic option for ponderal loss sustained in individuals with body mass index (BMI) over or equals 35 Kg/m² associated with comorbidities and BMI over or equals 40 Kg/m² without comorbidity. This study has been delineated with the purpose of evaluating the frequency of infeccious adverse events, mainly the surgical site infection (SSI) and the risk factors to develop SSI in patients submitted to gastroplasty. 128 promptuaries have been analysed. They were submitted to gastroplasty through Roux-en-Y gastric bypass technique, by laparatomic via, containing information about the main risk factors in obese patients and some post-surgical complications. Among the adverse events evaluated, it has been observed that the SSI frequency was 10,9%, the urinary tract infection (UTI) was 0,8% and there has been no registered case of pneumonia. It is noticed that the frequency of significancy to SSI was, in the univaried analysis, the internment period of time, systemic arterial hypertension (SAH), hypothyroidism, sort of surgical procedure, either with or without surgery associated with gastroplasty, and the seroma in surgical wound, all of them with p < 0,05. In the multivaried analysis, the risk factors with p < 0,05, were sort of surgical procedure, either with of without surgery combined to gastroplasty, considering that the chance for someone who has undergone associated surgery to have SSI is 7,25 times higher if compared to the ones in whom only the gastroplasty has been accomplished. The other risk factor was hypothyroidism, in which the study has shown that people who have hypothyroidism have the chance of having SSI 9,78 times more than the ones who dont have.[Key words: obesity; gastroplasty; Roux-en-Y gastric bypass; surgical site infection; risk factors.]